In vitro antibacterial activity of Spirulina platensis extracts against clinical isolates of Salmonella enterica serovars Typhi and Paratyphi (SUBP03) (Stamford Journal of Microbiology, 2016)
Natural therapy has its inherent attraction in that there are limited side-effects. Spirulina platensis, a naturally occurring algae, has been reported to have more than one therapeutic advantage. It is also used as a source of natural protein and vitamins in many parts of the world. In the present investigation, the antimicrobial activity of S. platensis against clinical isolates of Salmonella enterica serovar Typhi (n=17) and Paratyphi (n=3) was investigated. Ethanolic and chloroform extracts of S. platensis (40 mg/mL) were investigated for antimicrobial effect. Variable zones of inhibition were observed for the former extract whereas the latter did not show any inhibitory effect on growth of the test organism. Diameters of the zones of inhibition were 9.7-14.0 mm for S. Paratyphi and 9.5-16.0 mm for S. Typhi. The presence of zones of inhibition at the concentration of 40 mg/ml of the extract used is promising towards developing a natural remedy against infections with S. enterica serovars Typhi and Paratyphi.Stamford Journal of Microbiology, Vol.5(1) 2015: 22-25